The Fantastic Cutaway Book of Spacecraft - Hawkes, Nigel; Nang Chan Yeema (Brookfield, CN USA The Millbrook Press, 1995)
Cutaway illustrations and text reveal how the space shuttle and other spacecraft work and what astronauts do in space.
Keywords: Juvenile Nonfiction